2005
DOI: 10.1007/s10546-004-7403-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of surface albedo and soil thermal parameters with soil moisture content at a semi-desert site on the western Tibetan Plateau

Abstract: Almost three years of continuous measurements taken between January 2001 and May 2003 at the Gaize (or Gerze) automatic weather station (32.30°N, 84.06°E, 4420 m), a cold semi-desert site on the western Tibetan Plateau, have been used to study seasonal and annual variations of surface albedo and soil thermal parameters, such as thermal conductivity, thermal capacity and thermal diffusivity, and their relationship to soil moisture content. Most of these parameters undergo dramatic seasonal and annual variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…[23] The best fit coefficients A = 0.31, B = 12.7 and C = 0.15 are in the range of values found by Lobell and Asner [2002], but Wang et al [2005] reported a much lower value for the B coefficient (B = 3.52, clay soil type).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] The best fit coefficients A = 0.31, B = 12.7 and C = 0.15 are in the range of values found by Lobell and Asner [2002], but Wang et al [2005] reported a much lower value for the B coefficient (B = 3.52, clay soil type).…”
Section: Resultsmentioning
confidence: 99%
“…[11] To the authors' knowledge, the only in situ study after Idso et al [1975] is reported by Wang et al [2005], who also showed that bare soil albedo dependence on soil moisture on the Tibetan Plateau is nonlinear, but did not observe an opposite trend at high water content (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Both in situ measurements and remote sensing data from satellite and aircraft platforms have shown that BSA is strongly dependent on SZA [42][43][44][45]. Figure 9b,d show the BSA simulations with different SZAs, which exhibits obvious spatial variation characteristics corresponding to the mean slope distribution (shown in Figure 9a).…”
Section: Bsa Variation With Szamentioning
confidence: 96%
“…3c) and, therefore, are characterized by lower albedo. While albedo may have both a negative and a positive dependence on vegetation density depending on the color of bare soil that characterizes the region of study (Rechid et al, 2009), its dependence on soil moisture is clearer, wet terrain usually being less reflective than dry terrain (Lobell and Asner, 2002;Wang et al, 2005). For soil-vegetation systems, less absorbed net energy means less available energy for sensible heating and for evaporating water.…”
Section: Effect Of Vegetation On Albedomentioning
confidence: 99%